2011
DOI: 10.1111/j.1523-5378.2011.00860.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Functional Activity of Murine Monoclonal Antibodies Specific for α1,6-Glucan Chain of Helicobacter pylori Lipopolysaccharide

Abstract: Anti-α1,6-glucan mAbs could have potential application in typing and surveillance of H. pylori isolates as well as offer insights into structural requirements for the development of LPS-based vaccine against H. pylori infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…For example, the HP0826 mutant in SS1 strain, which is devoid of Lewis antigen, is still able to colonise the host, although less efficiently compared to the wild-type [16,35]. The DD-heptan and the glucan of the O-antigen are not essential for colonisation [19,33,47], while the HP0479 mutant truncated at the Hep residue of the Trio resulted in loss of colonisation ability [22]. The variability of the O-antigen beyond the conserved Trio may enable H .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the HP0826 mutant in SS1 strain, which is devoid of Lewis antigen, is still able to colonise the host, although less efficiently compared to the wild-type [16,35]. The DD-heptan and the glucan of the O-antigen are not essential for colonisation [19,33,47], while the HP0479 mutant truncated at the Hep residue of the Trio resulted in loss of colonisation ability [22]. The variability of the O-antigen beyond the conserved Trio may enable H .…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that 44.7 % of Chilean H. pylori isolates expressed a1,6-glucan, a polymeric component of the outer core region of LPS (Harrison et al, 2011). Co-expression of a1,6-glucan with Le x and/or Le y antigens in the majority of H. pylori strains examined suggests the importance of this LPS component in the pathogenesis of H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…The wells were then fixed with methanol and blocked with 200 ml Milk Diluent/Blocking solution (MDB) (KPL) for 2 h at 37 uC. Subsequently, the wells were incubated for 2 h at 37 uC with either 100 ml anti-Le a , -Le b , -Le x or -Le y mAb solution (Signet Laboratories) diluted 1 : 200 in MDB, 100 ml 1C4F9 ascites (anti-a1,6-glucan mAb) (Harrison et al, 2011) diluted 1 : 500 in MDB or rabbit anti-CagA antibody (Austral Biologicals) diluted 1 : 100 in MDB. This was followed by incubation with horseradish peroxidase (HRP)-conjugated anti-mouse IgG+IgM (Caltag) diluted 1 : 1000 in MDB for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…LPS Outer Core Structures in Other H. pylori strains. H. pylori strain J99 outer core is based on reference ; strains 11637(O:1)/P466/H428/H507/UA915/UA948/UA955/J223/CA2/CA4/CA5/CA6/F‐58C/F‐15A/R‐58A/F‐58C/GU2/R‐7A/H607 are based on and n = 2–3; strain PJ1 is based on reference ; PJ2 is based on references , O‐antigen is devoid and glucan: n = 3–9; strains O:6 and MO19 are based on references and m = 5, n (heptan) = 2, and n (glucan) = 2–3. For simplicity, lipid A, the inner core, and the O ‐antigen are not indicated.…”
Section: Structure and Biological Roles Of The Core Oligosaccharidementioning
confidence: 99%